(untitled) (International Journal of Physiotherapy, 2015)
Background: In the recent industrial set up, plantar fasciitis is one of the commonest problems faced by workers. It occurs mainly in the prolonged standing workers. There are some studies where some authors mentioned about interferential therapy as a treatment modality in plantar fasciitis but there is no such evidence supporting the use of IFT. Here comes the need of the study to find out the effects of the interferential therapy and also to find out whether the conventional therapy and interferential therapy are effective in plantar fasciitis for industrial workers. The aim of the study is to find out the benefit of the interferential therapy with the conventional therapy and also use conventional therapy alone for industrial worker in case of planter fasciitis. Methods: A sample of 30 subjects were distributing randomly in two groups. These subjects were referred by the consultant physician and orthopedic surgeon. All the subjects were signed a consent form prior to participation in the study. Before receiving any intervention, on day zero outcome measures assessment were carried out for both groups subjects by VAS (Visual analog scale) for pain measurement, FFI (Foot Function index ) scale for activity limitation scores and goniometric measurement of active dorsi-flexion of ankle joint. Range of Motion (ROM) measurement for both group A and B were taken usual in slandered goniometry according Martin and White. On day 15th, all outcome measures re-assessment will be carried out for the result. Results: In comparison of both interventions group B (IFT with conventional therapy) is more effective in decreasing pain (p = 0.00) improving functional ability (p = 0.00) than group A (only conventional therapy). For ROM, t = -0.642 the difference is not significant (p = 0.526). It has been inferred that conventional therapy and IFT with conventional therapy are equally effective for improving ROM. Conclusion: In conclusion, this study indicating that there is a significant difference in the effectiveness of Interferential therapy over conventional therapy in plantar fasciitis for industrial workers. Even though improvement in range of motion is not differing in both group, pain and functional improvement is more in the group treated with IFT.